Textbooks and School Library : Provision in Secondary Education in Sub-Saharan Africa - World Bank (Washington, DC : World Bank, 2012)
This study discusses secondary textbook and school library availability in Africa, its cost and financing, and its distribution and publishing. The study objective is to analyze the issues and provide some options and strategies for improvement. Reforms are urgently required in the secondary school systems of most African countries in order to: (a) reduce the number of textbooks and reference books required by secondary education curricula; (b) reduce the unit costs of textbooks; (c) increase the target book life thus increasing cost amortization and reducing annual textbook fees/budgets; (d) increase the financing allocated to textbook provision from either government or parents and; (e) ensure that curricula change does not make expensive materials redundant too early or too often. The conclusion to be drawn is that if a reliable market exists local publishing can develop to service it, even in direct competition with multinationals. The market does not necessarily have to be large. The critical factor is predictability. If publishers are confident that funding will be available, from whatever source, year after year then local publishing will emerge to serve that market. This is perhaps most clearly demonstrated in Botswana where a tiny but reliable and reasonably predictable secondary school sector has five competing approved textbooks in some secondary subjects.